The Impact of Regional FTA on Export of Manufactured Goods: The Implementation of Gravity Model in Indonesia - Marcelina Ribka Feonie Br. Siahaan; I Gede Agus Ariutama (Jurnal Ekonomi dan Studi Pembangunan, 2021)
Indonesian exports have not shown their best performance since Indonesian exports are still based on raw commodities, not manufactured commodities, causing Indonesia to experience a negative trade balance. Therefore, this study aims to investigate the impact of the six regional FTAs applied in Indonesia and related trade factors on Indonesian exports of manufactured goods with 40 partner countries using gravity model during 2002-2019 as a means of evaluation. The result indicates that the regional FTA has positive impact on Indonesian exports of manufactured goods. It also indicates that the regional FTA only causes trade creation effect. Furthermore, Gross Domestic Product (GDP) of two countries, economic distance, trade openness and the effective real exchange rate of partner countries significantly affect Indonesian exports of manufactured goods. Thus, it can be concluded that regional FTAs in both countries along with economic growth of Indonesia and partner countries, economic distance, trade openness and real effective exchange rate of partner countries are advantageous for Indonesian trade policy to increase the exports of manufactured goods.